The Influence of Education, Skills, and Motivation on Productivity and Performance with Competence as an Intervening Variable: Human Resource Management - Hedi, Tubagus Hedi Saepudin; Nani Sudiarti (Dinasti International Journal of Management Science, 2024)
The article The Influence of Education, Skills and Motivation on Productivity and Performance with Competence as an Intervening Variable is a scientific literature review article within the scope of human resource management science. This article aims to create a hypothesis regarding the relationship between factors, which can then be used for further research in the field of human resource management. Descriptive qualitative research methodology was used in this research. The data used in this research comes from previous research which is still relevant to the current investigation. Data was collected from leading academic online platforms, including Publish or Perish, Google Scholar, digital reference books, and Sprott journals. The findings of this research are as follows: 1) Education influences productivity; 2) Skills influence productivity; 3) Motivation influences productivity; 4) Education influences performance; 5) Skills influence performance; 6) Motivation influences performance; 7) Education influences competency; 8) Skills influence Competency; 9) Motivation influences Competence; 10) Competence influences Productivity; and 11) Competency influences performance.